Pengaplikasian Sistem Penuaian Air Hujan di Tapak Semaian UTHM - Saiful Bahry, Mohammad Firdaus; Shareh Musa, Sharifah Meryam; Zainal, Rozlin; Kassim, Narimah; Mohd Noh, Hamidun (Research in Management of Technology and Business, 2021)
Rainwater Harvesting System (SPAH) is one of the best management methods applied in Malaysia. This is because of its ability to be a source of alternative water supply that is safe to use and free. However, the issue of wastage of treated water and lack of clean water resources is often a contentious issue in Malaysia. SPAH is still not fully applied in the agricultural sector and is considered trivial by some communities. This study aims to analyze how an efficient SPAH design can be built and help its users, namely the UTHM Nursery in saving the use of treated water while reducing water bills. UTHM Nursery has been selected as a study area where it is one of the places that need a lot of water use. The approach of this study is qualitative, involving the UTHM Development and Maintenance Office (PPP UTHM) which is assigned to take care of the affairs of the nursery. Observations and fieldwork will be done to obtain the appropriate SPAH design selection data such as catchment area, types of building materials, rainfall distribution data in the area and so on. Data analysis will be done using the storage water tank capacity calculation formula obtained from the Department of Irrigation and Drainage (DID) and modeled using Revit software. Based on the results of this study, the application of SPAH in the UTHM Nursery will help in providing alternative water supply, save water bills in UTHM and reduce the cost of its application. Therefore, sustainable water use will be able to be created and even the maintenance cost of SPAH which has been a problem can also be resolved with the availability of efficient SPAH design and suitable for the study area.